Synthesis and Characterization of Transition Metal Complexes of 1,2-Bis(3,5-Dimethylpyrazol-1-yl)-1,2-Ethanediol; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Anosova G. A.; Matveevskaya V. V.; Pirmanova N. A.; Potapov A. S. Andrey Sergeevich (Chemical Engineering and Technology, 2016)
Title screen